2018
DOI: 10.1002/smll.201804150
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient and Ultrasensitive Large‐Area Flexible Photodetector Based on Perovskite Nanowires

Abstract: Hybrid organic–inorganic perovskites have shown exceptional semiconducting properties and microstructural versatility for inexpensive, solution‐processable photovoltaic and optoelectronic devices. In this work, an all‐solution‐based technique in ambient environment for highly sensitive and high‐speed flexible photodetectors using high crystal quality perovskite nanowires grown on Kapton substrate is presented. At 10 V, the optimized photodetector exhibits a responsivity as high as 0.62 A W−1, a maximum specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 49 publications
3
95
0
Order By: Relevance
“…1 Their effective photon absorption, 2 low exciton binding energy, 3 and tunable bandgap (1.5-2.2 eV) 4 are advantageous for applications such as light-emitting diodes (LEDs), [5][6][7] photovoltaics (PVs) [8][9][10] and photodetector devices. [11][12][13] Albeit the remarkable progress from the past few years, organic-inorganic halide perovskite (OIHP) processing and its stability under ambient conditions remain an open challenge towards commercialization. The shelf-lifetime of OIHP, especially CH 3 NH 3 PbI 3 -based devices under ambient air conditions, is very short, 14 and their performances decrease rapidly due to the extrinsic and intrinsic instabilities of the halide perovskites.…”
Section: Introductionmentioning
confidence: 99%
“…1 Their effective photon absorption, 2 low exciton binding energy, 3 and tunable bandgap (1.5-2.2 eV) 4 are advantageous for applications such as light-emitting diodes (LEDs), [5][6][7] photovoltaics (PVs) [8][9][10] and photodetector devices. [11][12][13] Albeit the remarkable progress from the past few years, organic-inorganic halide perovskite (OIHP) processing and its stability under ambient conditions remain an open challenge towards commercialization. The shelf-lifetime of OIHP, especially CH 3 NH 3 PbI 3 -based devices under ambient air conditions, is very short, 14 and their performances decrease rapidly due to the extrinsic and intrinsic instabilities of the halide perovskites.…”
Section: Introductionmentioning
confidence: 99%
“…It is also known that the crystallization of PNCs is another key parameter in relation to stability . Yuan's group reported that smaller clusters of cuboid MAPbI 3 NCs are more stable than the larger ones .…”
Section: Optoelectronic Propertiesmentioning
confidence: 99%
“…Figure E showed that the currents through MAPbI 3 NRs PDs under dark and irradiation conditions existed no significant decrease at different bending curvatures, proving the initial mechanical flexibility of MAPbI 3 NRs FPDs. In addition, Cloutier and co‐workers displayed the fabrication of 1D pseudohalide perovskite nanowires networks and their application in solution‐based large‐scale FPDs . PMMA film was spin‐coated on the perovskite layer to offer a passivation of the surface defects and/or protection from the environment.…”
Section: Flexible Photodetectors Based On Metal Halide Perovskitesmentioning
confidence: 99%
“…D, I‐V curves of flexible photodetectors with/without PMMA protective layer under dark and light states. Reproduced with permission . Copyright 2018, WILEY‐VCH.…”
Section: Flexible Photodetectors Based On Metal Halide Perovskitesmentioning
confidence: 99%